Influenza vaccine effectiveness within prospective cohorts of healthcare personnel in Israel and Peru 2016–2019. Issue 47 (16th November 2021) - Thompson, Mark G.; Soto, Giselle; Peretz, Alon; Newes-Adeyi, Gabriella; Yoo, Young M.; Hirsch, Avital; Katz, Mark A.; Tinoco, Yeny; Shemer Avni, Yonat; Ticona, Eduardo; Malosh, Ryan; Martin, Emily; et al.
Abstract: Background: There are limited data on influenza vaccine effectiveness (IVE) in preventing laboratory-confirmed influenza illness among healthcare personnel (HCP). Methods: HCP with direct patient contact working full-time in hospitals were followed during three influenza seasons in Israel (2016–2017 to 2018–2019) and Peru (2016 to 2018). Trivalent influenza vaccines were available at all sites, except during 2018–2019 when Israel used quadrivalent vaccines; vaccination was documented by electronic medical records, vaccine registries, and/or self-report (for vaccinations outside the hospital). Twice-weekly active surveillance identified acute respiratory symptoms or febrile illness (ARFI); self-collected respiratory specimens were tested by real-time reverse transcription polymerase chain reaction (PCR) assay. IVE was 100 × 1-hazard ratio (adjusted for sex, age, occupation, and hospital). Results: Among 5, 489 HCP who contributed 10, 041 person-seasons, influenza vaccination coverage was 47% in Israel and 32% in Peru. Of 3, 056 ARFIs in Israel and 3, 538 in Peru, A or B influenza virus infections were identified in 205 (7%) in Israel and 87 (2.5%) in Peru. IVE against all viruses across seasons was 1% (95% confidence interval [CI] = −30%, 25%) in Israel and 12% (95% CI = −61%, 52%) in Peru. Conclusion: Estimates of IVE were null using person-time models during six study seasons in Israel and Peru.